Produksi Video Klip Multiplek Lagu â€œSemalam di Cianjurâ€ Berbasis Multimedia - Hendraningrat, R Wahyu; Hepy Urbani, Yunanto (APMMI - Asosiasi Profesi Multimedia Indonesia, 2014)
Abstract :Â Multiplex is a special type of karaoke songs that have the ultimate guide vocal, which helps to learn the track. Vocals were recorded on only one side of the stereo channels, making it possible to be processed with Sony Vegas software into a video clip. The issues raised in the study is not much research on the production of a video clip discusses the multiplex, so the lack of a reference sample for the study multiplex. The goal for the Produce video clips multiplex song